International visualization analysis of research hotspots and development trends in the study of clinical decision support systems utilizing CiteSpace - Meixuan Song; Dong Liu; Dong Liu (Frontiers in Medicine)
ObjectiveThis study aims to elucidate the current status and trends in clinical decision support systems (CDSS). It will analyze the direction of research development in this field and provide valuable references for future research and the application of CDSS.MethodsWe conducted a search of the Web of Science Core Collection database from January 2014 to May 2024 to identify relevant literature on clinical decision support systems. CiteSpace (6.2. R4) software was utilized to visualize and analyze various aspects of the included literature, including publication volume, country of origin, authors, institutions, cited literature, keywords, and keyword clustering, and to generate corresponding graphs.ResultsA total of 2,668 articles were ultimately included in this study. The scholar with the highest number of publications is Professor Adam from the Department of Biomedical Information at Vanderbilt University in the United States. The top five countries contributing to this research are the United States, the United Kingdom, Germany, the Netherlands, and China. Based on an analysis of cited literature and keyword clustering, the research primarily focuses on predicting biochemical recurrence, cardiovascular disease, clinical guidelines, evidence-based computerized decision support systems, and intensive care units. The prominent topics in this field include artificial intelligence, natural language processing, venous thromboembolism, user-centered design, and emergency medicine.ConclusionResearch on CDSS is demonstrating an upward trend and shows promising development prospects. Artificial intelligence, natural language processing, and user-centered design are the future trends.